Quantification of pulmonary arterial pressure with 4D flow cardiac MRI velocity mapping in patients with suspected pulmonary hypertension: Comparison with right heart catheterization - Charlotte Dantoing; Roger Bouzerar; Yohann Bohbot; Isabelle Mayeux; Raphaël Pichois; Cédric Renard (PLoS ONE, 2026)
Objectives 4D flow MRI is becoming a promising tool to assess pulmonary hypertension which remains a progressive fatal disease. The aim of this study was to compare the quantification of pulmonary arterial pressure derived from 4D flow MRI with right heart catheterization in patients with pulmonary hypertension. Methods Thirty-two patients (22 men, 10 women, mean age 62.6 years old) with known or suspected pulmonary hypertension were enrolled in this prospective study. Subjects were split into two consecutive groups, with the first 22 subjects dedicated to analysis and the last 10 subjects dedicated to validation. All patients underwent right heart catheterization and cardiac MRI examinations. Pulmonary arterial pressures were measured by catheterization. An accelerated kat-arc 4D flow MRI sequence allowed the analysis of cardiac blood and pulmonary artery (PA) flows. Multivariate linear regression models were obtained using stepwise, bottom-up and top-down covariate selection procedures. Results Using right heart catheterization as reference, the multivariate estimates of mean (mPAP) and systolic (sPAP) pulmonary arterial pressures only included 4D flow MRI parameters: mean helicity in right ventricle (RV), mean vorticity in right atrium (RA) and maximum cross-sectional PA area (A max _PA). The models yielded mPAP = 0.04.A max _PA + 0.061.mean_helicity_RV – 2.42 (R² = 0.69) and sPAP = 0.066.A max _PA + 0.134.mean_helicity_RV – 0.613.mean_vorticity_RA + 23.98 (R² = 0.80). Bland-Altman bias were 0.42 and 0.38 mmHg, respectively. Conclusion This study suggests that kat-arc accelerated 4D flow MRI is a potential non-invasive technique for pulmonary arterial pressure estimation. Therefore, this short-duration sequence could become a useful diagnostic and follow-up exam for patients with pulmonary hypertension.